Evidence for a Common Multi-Modal Learning Style in Young Adults? A Psychometric Investigation of Two Modality-Specific Learning Style Inventories - Aslaksen, Karoline; Haga, Monika; Sigmundsson, Hermundur; Lorås, Håvard (Frontiers in Education, 2020)
A well-known hypothesis amongst educators and the general public is that matching instructional method with an individual’s modality-specific learning style improves learning. Several critical reports in the past decade, however, have shown that the psychometric properties of the inventories applied to establish modality-specific learning styles have been poorly validated. Furthermore, theoretical development has challenged the theoretical basis for the modality-specific learning style model. Thus, the aim of the current study was to examine the psychometric properties and relationship between, two modality-specific learning style inventories: the Barsch Learning Style Inventory (BLSI) and the Learning Style Survey (LSS). University students (n = 242) completed the two inventories, and their responses were subjected to confirmatory and exploratory factor analysis, as well as analysis of inter-item agreement (internal consistency). The results failed to support the expected three-factor measurement model and thus indicated questionable reliability and factorial validity of the two inventories. Analysis of inter-correlations between factors from the two inventories resulted in a one-factor solution explaining up to 40% of the variance, which is discussed as emerging through an overall multimodal learning style.